Corrosion Inhibition Mechanism Based on Adsorption Isotherm Model From Water Extract of Merkubung (Macaranga gigantea) Bark Extract on Mild Steel in Sulfuric Acid Solution - Diah Riski Gusti; Nelson Nelson; Intan Lestari; Putri Ramadhanti; Ria Gracia Sibarani (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
The phenolic chemicals found in water extract of Merkubung bark (WEMB) can be employed as corrosion inhibitors. The corrosion inhibition mechanism by WEMB can be studied using an adsorption isotherm model. The Langmuir adsorption isotherm model has an R2 value that was closest to 1 one compared to the Freundlich, Temkin, Florry Huggins, and Frumkin adsorption isotherm models, as shown by an analysis of the adsorption isotherm model. Due to the interaction between the WEMB and the steel surface, the adsorption isotherm model reveals that the inhibitor of WEMB on the surface coating of mild steel tends toward chemisorption.